2017
DOI: 10.3389/fneur.2017.00181
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sites Ultrasonography of Peripheral Nerves in Differentiating Charcot–Marie–Tooth Type 1A from Chronic Inflammatory Demyelinating Polyradiculoneuropathy

Abstract: IntroductionMultiple sites measurement of cross-sectional areas (CSA) by ultrasound was performed to differentiate Charcot–Marie–Tooth type 1A (CMT1A) and chronic inflammatory demyelinating polyradiculoneuropathy (CIDP).MethodsNine patients with CMT1A, 28 patients with CIDP, and 14 healthy controls (HC) were recruited prospectively. Consecutive ultrasonography scanning was performed from wrist to axilla on median and ulnar nerves. CSAs were measured at 10 predetermined sites of each nerve.ResultsCMT1A had sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…Cytokines are mediators of the immune communication that may cross the blood-brain barrier (BBB) and provide a mechanism by which the peripheral immune system may directly influence the CNS ( 30 ). In a recent study, we demonstrated a pro-inflammatory immune response with elevated inflammatory cytokines both in serum during disease and post-mortem in the CNS of ALS patients ( 31 ). However, immune response in ALS cannot be clearly dichotomized to a purely pro- or anti-inflammatory state, as cytokines are often pleiotropic, and their function may change over time and depend on concentration and specific disease context.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Cytokines are mediators of the immune communication that may cross the blood-brain barrier (BBB) and provide a mechanism by which the peripheral immune system may directly influence the CNS ( 30 ). In a recent study, we demonstrated a pro-inflammatory immune response with elevated inflammatory cytokines both in serum during disease and post-mortem in the CNS of ALS patients ( 31 ). However, immune response in ALS cannot be clearly dichotomized to a purely pro- or anti-inflammatory state, as cytokines are often pleiotropic, and their function may change over time and depend on concentration and specific disease context.…”
Section: Discussionmentioning
confidence: 95%
“…Initial TNF-beta (LTA, lymphotoxin-alpha) levels negatively correlated with survival and were found at higher levels in shorter surviving ALS patients upon treatment initiation. G-CSF application led to reduction in TNF-beta, a pro-inflammatory cytokine and common cell death effector found to be increased in ALS sera ( 31 ). TNF-alpha was borderline increased in patients with shorter survival (trend) and G-CSF led to an increase in its serum levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, nerve ultrasound has been used to detect morphological abnormalities of the peripheral nerves in CIDP. Most studies have been cross‐sectional and have shown different patterns of nerve morphological changes in patients with CIDP, including moderate cross‐sectional area (CSA) enlargement, segmental prominent enlargement, and little enlargement . However, few studies have reported how nerve morphology changes over time in CIDP.…”
mentioning
confidence: 99%
“…Most studies have been cross-sectional and have shown different patterns of nerve morphological changes in patients with CIDP, including moderate cross-sectional area (CSA) enlargement, segmental prominent enlargement, and little enlargement. 2,3 However, few studies have reported how nerve morphology changes over time in CIDP. Zaidman et al 4 showed that, in CIDP, enlarged nerves normalized or decreased in size with remission.…”
mentioning
confidence: 99%